Errância de gênero: percursos para uma relação de desejo entre nós - Carvalhedo, Ierê Fraga (2021)
This research starts from the investigation on the notion of identity that has guided the project of affirmation of gender identities in Brazil, João W. Nery Law Project / Gender Identity Law - PL5002 / 2013 (BRASIL, 2013). This project was proposed for the recognition and protection of the Human Rights of vulnerable people who are susceptible to current power structures. Besides the State, labor markets create and manipulate gender differences, transforming the body and identity into marketable products. It is in this context that terms such as transfake and cisfake emerge, announcing that the fictional split between body and mind, nature and culture, persists. The corpus of this dissertation is a personal experience of voluntary testosterone intake. We share the problems and experiences which, in dialogue with political bibliographies, undermine the aforementioned dichotomies and the orderly relationship between body and environment. These issues illuminate the power relations between the subject and the current neoliberal economy. As a theoretical foundation, we discuss relationships proposed between anthropomorphic images present in Georges Bataille work (2013) that question modern rationality. We discuss Corpomedia theory, by Christine Greiner and Helena Katz (2005), which analyzes the body in its coevolutionary processes with the environment. We discuss aspects of the sexuality debate present in the work of Michel Foucault (2015), Judith Butler (2017) and Paul B. Prececiado (2018). We analyze the discussion, launched by Achille Mbembe (2017), regarding cultural hostilities that cause dehumanized living conditions. We discuss the relations of otherness in art, through some notions of the researcher Christine Greiner (2017) that have caused clashes within social movements. With this research, we wish to collaborate with a side of the debate that has been strengthened, recently, in Brazil and internationally, despite the macro-political prohibitions it faces